How can Secondary Thromboprophylaxis in High-Risk Pregnant Patients be Improved?. (February 2022) - Stanciakova, Lucia; Dobrotova, Miroslava; Holly, Pavol; Zolkova, Jana; Vadelova, Lubica; Skornova, Ingrid; Ivankova, Jela; Samos, Matej; Bolek, Tomas; Grendar, Marian; Danko, Jan; Kubisz, Peter; et al.
Low-molecular-weight heparin (LMWH) is suggested for thromboprophylaxis in pregnant women with previous venous thromboembolism (VTE) . Anyway, there is only limited amount of studies evaluating the effect of LMWH on hemostatic parameters during pregnancy of patients with previous VTE and the need of secondary thromboprophylaxis. We therefore provide results of prospective and longitudinal assessment of changes in hemostasis in high-risk pregnant women at four times during pregnancy (T1–T4) and one time after the postpartum period (T5) used for individualized modification of thromboprophylaxis. In this study, the results of coagulation factor VIII (FVIII) and protein S (PS) activity, ProC Global ratio and anti-Xa activity were evaluated. Despite the thromboprophylaxis, an increased predisposition to thromboembolic complications was detected (significant increase in FVIII activity and decrease in PS function, ProC Global ratio not normalized even after the postpartum period – p < .0001 between controls and T5 for PS and ProC Global). These results indicate that hemostasis may not be restored even 6 to 8 weeks after delivery and pose the question when is it safe to withdraw the anticoagulant thromboprophylaxis in high-risk patients with prior VTE.